Credit default swaps and corporate ESG performance - Zhao, Ran; Zhu, Lu (Journal of Banking & Finance, 2024)
This study finds that credit default swap (CDS) trading positively affects a firm's environmental, social, and governance (ESG) performance. This effect is more prominent in ESG strengths than ESG concerns. The proposed empirical connection remains valid across endogeneity-controlling methodologies, model specifications, and ESG performance measures. The effect is stronger for firms with stronger bank relationships, higher debt dependence, and more restrictive covenants. Furthermore, improvement in ESG performance is more pronounced for firms with more free cash flow, lower institutional ownership, and higher financial constraints. Our findings reveal the real effects of CDS trading on firm ESG performance.